Anti-cancer activity of Mebendazole, Metformin and Apricoxib in HT-29, MDA-MB-231 HelaandMCF-7cell lines: Preclinical trial - Fatima Rizvi, Farah Asad, Lubna Shaukat, Muhammad Atif Siddiqui, Farida Qadir, Abdul Qadir, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To look at anti-cancer effects of a variety of novel drugs on a variety of cancerous cell lines in the quest for a more inexpensive and effective anti-cancer treatment. Methodology: The research was carried out in conjunction with PCMD at JPMC's BMSI Department of Pharmacology. The experiment lasted about eight months (from April to November 2016). Noninvasive estrogen-dependent tumours, invasive estrogen-independent breast cancer, colorectal cancer, and cervical cancer were all depicted using MCF-7, HT-29, MDA-MB-231and HeLa cell lines, in that order. The MTT assay was used to improve the drugs' anticancer or antiproliferative efficacy in vitro. Using the MTT test, we determined the vitality of all treated tumour cell lines as well as the IC50 values of each chemical against all malignant cell lines. Results: This study demonstrated thatMetformin significantly decreased the survivability of MCF7, HT-29, MDA-MB-231, and Hela cell lines when compared to Apricoxib and Mebendazole. As a result, comparing the IC50 values of the studied agents for each of the evaluated treated cells backed up this claim. Hence, for Hela(p=0.386), MCF-7 (p=0.083), and MDA-MB-231 (p=0.083) cell lines but pochoc analysis revealed no significant differences in IC50 values of Metformin and Methotrexate. Conclusion: When compared to Apricoxib and Mebendazole, Metformin has a significant effect on the survivability of the cell lines studied. Metformin, as a result, would have been a wonderful chemotherapeutic addition Keywords: Cell lines, In vitro, MCF-7, Hela, MDA-MB-231